Redescription of Alonella lineolata Sars, 1901 (Crustacea, Cladocera, Chydoridae) and its translocation to the subfamily Aloninae and to the new genus Bergamina gen. nov. - Elmoor-Loureiro, Lourdes M.a.; Santos-Wisniewski, Maria José; Rocha, Odete (Zootaxa, 2013)
Alonella lineolata Sars 1901 (Anomopoda, Chydoridae) was described from a single female found in an aquarium prepared with dried mud from São Paulo, Brazil, and just recently this taxon has been reported again. The taxonomic status of A. lineolata was previously questioned, but re-evaluation was not possible until now due to the lack of specimens. The present paper described parthenogenetic females, based on specimens collected in a small pond at Pradópolis, state of São Paulo, and a specimen was selected as neotype. The head pores, mandibles, and the trunk limb morphology revealed that this species belongs to the subfamily Aloninae, instead of Chydorinae, as presumed by Sars. Despite its Alona-like aspect, this species presents a unique combination of characters, leading to its assignment to a new alonine genus, Bergamina gen.nov.